The Effect Insole Usage on Children Balance with Flatfoot Condition - Narastiti, Kerub Dion Sihwening; Dwi Setyawan, Dwi; Ningsih, Cica Tri Mandasari (Journal of Prosthetics Orthotics and Science Technology, 2023)
Background: Flatfoot conditions cause children to experience balance problems due to musculoskeletal disorders of the foot. Cases of flatfoot are prevalent in many children and can interfere with their growth and development, potentially reducing their quality of life in the future. Therefore, efforts are needed to improve children's balance. This study aims to determine whether the usage of insoles has an effect on the balance of children with flatfoot conditions at Banyuanyar 3 Elementary School. Methods and Subjects: By implementing gross motor training for children and utilizing arch support insoles, the study seeks to enhance children's balance ability. The research design is a quantitative experimental design with Randomized Controlled Trials (RCT), employing Single Blinding, and data collection through Pre-test and Post-test. The purposive sampling technique was used, with an intervention period of 30 days. The subjects included students from SD Negeri Banyuanyar 3, with a selected sample of 30 children from a population of 119 with flatfoot conditions. Standard interventions, such as rhythmic gymnastics, function as efforts to improve children's balance abilities and are applied to both the control and intervention groups, each comprising 15 children. The Pediatric Balance Scale (PBS) was used in this study to measure the level of functional balance in children. Results: The Wilcoxon test results for the treatment group indicated a P-value of 0.002 (<0.05), signifying a difference in balance ability between the pre-test and post-test in the treatment group. This indicates an improvement in balance among children using EVA insoles. Conversely, the control group's test results showed a P-value of 0.067 (P>0.05), suggesting no difference in balance ability between the pre-test and post-test in the control group. Therefore, based on this study, it can be concluded that the use of EVA insoles with arch support was found to improve the balance of children with flatfoot conditions.